Clinical Efficacy of Repetitive Transcranial Magnetic Stimulation Combined with Cognitive Training on Patients with Post Stroke Cognitive Impairment： A Meta-Analysis - LIU Changxing; GUO Xinyi; CHANG Xiang (康复学报)
ObjectiveTo evaluate the efficacy of repetitive transcranial magnetic stimulation (rTMS) combined with cognitive training on patients with post stroke cognitive impairment (PSCI) by Meta-analysis.MethodsData were searched and retrieved from the databases of PubMed, Embase, The Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Data, and Chinese Science and Technology Periodical Database (VIP). The randomized controlled trials (RCTs) of rTMS combined with cognitive training for the treatment of patients with PSCI were included, and the retrieval time was from database inception to June 2023. The primary outcome measures included Montreal cognitive assessment (MoCA), mini-mental state examination (MMSE), activities of daily living (ADL) scale and Rivermead behavioural memory test (RBMT). The quality of the literature was assessed by two investigators using the Cochrane risk of bias assessment tool, and Meta-analysis was performed using RevMan 5.3 software. Enumeration data were expressed as odds ratio (OR) or relative risk ratio (RR). Measurement data were expressed as mean difference (MD) or standardized mean difference (SMD), with 95% confidence interval (CI). The heterogeneity was determined according to the P value and I2 value. If P≥0.10 and I2≤50%, a fixed effects model would be used, and if P<0.10 and I2>50%, a random effects model would be used.ResultsA total of 23 RCTs with 1 788 patients were included, 895 patients in the control group and 893 patients in the experimental group. (1) MoCA scores: subgroup analyses by different treatments in the control group showed that MoCA scores in the experimental group were significantly higher than those in the control group [MD=1.78, 95% CI (1.18, 2.38), P<0.000 1; MD=3.30, 95% CI (3.01,3.58), P<0.000 01]; subgroup analyses by stimulation frequency showed that MoCA scores in the experimental group were significantly higher than those in the control group [MD=3.49, 95% CI (3.40, 3.57), P<0.000 01; MD=3.16, 95% CI (2.79, 3.53), P<0.000 01]. (2) MMSE score: compared with the control group, MMSE score in the experimental group was higher [MD=2.14, 95% CI (1.14, 3.15), P<0.000 1; MD=3.16, 95% CI (2.71, 3.60), P<0.000 01]. (3) ADL score: compared with the control group, ADL score in the experimental group was higher [MD=10.78, 95% CI (9.18, 12.38), P<0.000 01; MD=8.23, 95% CI (7.04, 9.41), P<0.000 01]. (4) RBMT score: compared with the control group, RBMT score in the experimental group was higher [MD=2.00, 95% CI (1.37, 2.63), P<0.000 01].ConclusionrTMS combined with cognitive training can improve cognitive function, intelligence state, behavioral memory ability and activities of daily living of stroke patients, which is recommended for clinical application.